How do food-derived satiety peptides regulate appetite? Insights into efficacy, assessment and mechanism - Ruiyang Yuan; Yuer Zhang; Yujia Lu; Yuchen Zhao; Xintong Yao; Rotimi E. Aluko; Na Zhang; Yuhao Zhang; Yu Fu (Trends in Food Science & Technology, 2026)

Storm-event nitrate export in a karst hillslope: Flow-path partitioning and hysteresis patterns - Na Feng; Jun Zhang; Fa Wang; Zhiyong Fu; Hongsong Chen (CATENA, 2026)

Fe3O4 supported on rabbit-tail grass-derived biochar for energy-efficient CO2 desorption: Synergistic effects of acid sites and carbon-assisted electron-driving mechanism - Lianming Wu; Anqi Jia; Xingyong Li; Senshen Yu; Xuexiang Fu; Na Liu; Yubao Chen (Biomass and Bioenergy, 2026)

From spice to functional ingredient: Linking flavor and bioactivity of Cumin (Cuminum cyminum L.) with processing and matrix effects - Haoyu Xiong; Na Zhang; Reham Kh Abdelmotaleb; Soottawat Benjakul; Yu Fu (Trends in Food Science & Technology, 2026)

Biological recovery of waste lithium-ion battery cathode materials: Recent advancements - Haolin Li; Senshen Yu; Shuaizhe Li; Mengke Dong; Yunke Wang; Huijun Fan; Yadong Wang; Xingyong Li; Na Liu; Xuexiang Fu; Di Cai; Yanliang Guo; et al. (Journal of Environmental Chemical Engineering, 2026)

Machine learning-enabled prediction of enzymatic saccharification of agricultural residues for biorefinery - Jiaxuan Tang; Zhiyuan Fu; Qiuli Chen; Na Li; Weiwei Huang; Yi Zhang; Hongye Li; Yunzi Hu (Chemical Engineering Journal, 2026)

A new strategy for steady-state butyric acid encapsulation: Mechanism of starch-lauric acid-protein-butyric acid complex formation, release characteristics and prebiotic properties - Yan Wang; Ruonan Fu; Kaiwen Wang; Tianyu Han; Lirui Sun; Xiushan Zhang; Zhenxing Wang; Jiaying Xin; Siew Young Quek; Na Zhang (Carbohydrate Polymers, 2026)

Coupling of rainband structure and intraseasonal monsoon variability shaping rainfall distribution during weak tropical cyclone Lupit (2021) - Qian Wang; Na Wei; Dajun Zhao; Jiaolan Fu; Yinglong Xu (Atmospheric Research, 2026)

Pomegranate Peel Polyphenols-incorporated PVA/CMC Hydrogels for High-efficiency Removal of Methylene Blue from Aqueous Solutions - Qihua Zhou; Chenyang Wang; Simin Xu; Ziyi Duan; Tiantian Fu; Zhonghai Ding; Na Li (Water, Air, & Soil Pollution, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Extrusion-induced structural reorganization of starch-ca HMB complexes for modulating starch digestibility and controlling nutrient release - Dandan Wang; Lulu Li; Yifan Fu; Ling Xin; Huili Tong; Dong Liang; Qingmin Kong; Na Zhang; Xiaofei Liu (Food Research International, 2026)

Unraveling the cholesterol-lowering mechanism of a Lactobacillus rhamnosus S_82 and xylo-oligosaccharides synbiotic in sour cream - Xuemeng Fu; Wenhao Zhao; Dongyao Li; Na Zhang; Miaoshu Wang; Xia Tang; Qinghai Sheng; Hongtao Tian; Chen Li (Food Microbiology, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Rational Design of Gi-biased CB1 Agonists for the Next Generation of Analgesic Drug - Na Ye; Zhi-Feng Shi; Fu-Hai Ji; Xue-Chu Zhen (Neuroscience Bulletin, 2026)

From alliinase to allicin: Insights into preparation, pungency and bioactivity - Xi Chen; Yuanfa Jiang; Na Zhang; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Trends in Food Science & Technology, 2026)

Screening of typical pollutants in groundwater polluted by nitrogen heterocyclic pesticides and removal mechanism of iron-doped biochar - Renchuan Fu; Kai Liu; Dan Qu; Yuqi Qi; Xiaochen Qi; Chih-Huang Weng; Yanru Hao; Na Liu; Chunyu Wen (Journal of Environmental Sciences, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Daily mortality prediction under compound environmental stressors: Comparing epidemiological time series models and machine learning models - Wanjie Wang; Xiaoyan Zhou; Na Li; Feng Chen; Jingqiao Fu; Zhiyang Su; Yuqing Yao; Xiaoyan Yuan; Sirui Lin; Mengfan Chen; Maji Gan; Jieming Zhong; et al. (Environmental Research, 2026)

Effects of PE microplastics on root morphology and soil nutrients with mechanisms of rhizosphere enrichment in Brassica rapa var. chinensis - Yifei Lin; Chenrui Zhao; Chengliang Li; Lei Hou; Na Liu; Yicheng Fu; Qian Zhang (Journal of Soils and Sediments, 2026)

Genome-Wide Identification of 33 Drought-Responsive P450 Genes in Sorghum Bicolor and Analyses of their Tissue-Specific Expression Under Abiotic Stress Conditions - Senjie Fu; Junxia Li; Na Qin; Ya Jing; Cancan Zhu; Shutao Dai; Chengyang Zhang; Chunyi Wang (Tropical Plant Biology, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Integrated in silico, in vitro, and machine learning pipeline for extraction of antioxidant peptides and lipids from fish viscera - Sirong Huang; Dongjing Wu; Na Zhang; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Benzo[a]pyrene lowers the sperm quality in male rats by downregulating the expression of ZMYND15 and ZMYND10 - Xinrui Zhao; Xiuxia Dong; Pengjuan Fu; Yongkang Chen; Na Liu; Bohe Wang; Xiaojuan Feng; Xiangli Li (Reproductive Toxicology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Flavor characterization of Chenxiang-type baijiu-Daoguang nianwu aged in wooden Jiuhai with different vintages integrating GC-E-nose, GC-IMS, GC-MS-O, ROAV and chemometrics approaches - Na Wang; Xiangyang Zhang; Li Xue; Zhen Zhang; Li Fu; Xuejiao Ren; Hui Zhang; Bo Zhang; Xiaoyu Jiang; Lili Zhang; Mei Wang (Food Research International, 2026)

Effects of different biomass amendments on the biogeochemical processes of arsenic transformation during tailings soil leaching: Insights into dissolved organic matter and arsenic-functional genes - Jun Zeng; Hong Wang; Qing Hu; Na Liu; Bowen Hu; Renchuan Fu; Longzhen Ding (Chemical Engineering Journal, 2026)

Subsurface stormflow concentration-discharge relationships reveal DOC and nitrate transport mechanisms across land uses in karst hillslopes - Na Feng; Jun Zhang; Fa Wang; Zhiyong Fu; Hongsong Chen (Journal of Hydrology, 2026)

Light absorption property, oxidative potential and chemical composition of organic carbon emitted from the combustion of representative coals in China - Hao Na; Shaojie Yang; Jianwei Zheng; Jingxuan Yang; Fu Li; Xiangli Nan; Wangjin Yang; Chong Han (Journal of Environmental Sciences, 2026)

An integrated in silico, in vitro, and machine learning pipeline for rapid discovery of antioxidant peptides and co-product lipids from goat liver - Dongjing Wu; Sirong Huang; Na Zhang; Mohammed Gagaoua; Yuhao Zhang; Yu Fu (Food Research International, 2026)

Provincial–level evaluation of pollution reduction and carbon mitigation in China based on Driving Force–Pressure–State–Impact–Response framework - Qiang Feng; Xiaomin Zhang; Jia Wu; Zeqiang Fu; Na Wu; Yanhua Wang (Atmospheric Pollution Research, 2026)

ACT001 alleviates sepsis-induced acute lung injury by downregulating PANoptosis via the JAK2/STAT3 pathway - Nana Zhang; Hewei Zhang; Jialu Ping; Na Shen; Tao Fang; Qiang Fu (Inflammation Research, 2026)

Unraveling the distribution and stability of deep soil organic carbon after long-term conservation tillage practices - Jianye Li; Yong Zhu; Na Li; Yunying Fang; Xiaolin Dou; Yuanyuan Lu; Xingyi Zhang; Bojie Fu; Chunlong Liu; Shuguang Liu; Xinqiang Liang (Soil and Tillage Research, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Insight the active sites and adsorption-desorption mechanism on red mud adsorbent for direct air capture of CO2 with excellent cycling performance - Na Gao; Jin Zhang; Ziyan chen; Bin Li; Mingli Fu; Daiqi Ye (Chemical Engineering Journal, 2026)

An enhanced cow-teat-detection model for automatic teat-cup-attachment devices - Mengjie Li; Juan Wang; Na Li; Yaju Liu; Xue Cheng; Xinpei Fu; Sirui Li (Biosystems Engineering, 2026)

Crustal structure and tectonic implications of the Southern Central Asian Orogenic Belt: New insights from gravity, magnetic, and magnetotelluric imaging - Chutong Chen; Na Li; Lingxiao Zhang; Hongying An; Chang’an Guo; Xing Fu; Songda Lei; Guicai Yang; Junjie Fan; Weiheng Yuan; Hao Wang; Bin Wang; et al. (Tectonophysics, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Design and optimization of triply periodic minimal surface structure flow channels in proton exchange membrane fuel cells based on genetic algorithm - Lirong Fu; Yiwen Tang; Jinyi Liu; Mingwei Li; Na Qiu (Fuel, 2026)

Pectic polysaccharides from Mongolian medicinal Hypecoum leptocarpum: Structure and ulcerative colitis amelioration via gut microbiota and intestinal inflammation regulation - Cunwuliji Na; Xiang Shi; Jicheng Fu; Jiahao Li; Hongyu Jiang; Zhiwei Guo; Hongyan Lai; Zhipeng Zhang; Longyan Zhao; Qingxia Yuan; Baoshun Zhang (Carbohydrate Polymers, 2026)

Three-dimensional suspension induction of porcine EPSCs into PGCs - Liming Yuan; Xiaolong Wu; Xiaoxiao Fu; Zuo Lei; Hongzhao Shi; Wenjie Xu; Yaya Zhao; Jiannan Li; Xueting Li; Lexi Gao; Na Li; Jinlian Hua (Theriogenology, 2026)

Mutant transcription factor CopR promotes LDB_RS05285 expression to suppress yogurt post-acidification and enhance texture stability - Wenhao Zhao; Xuemeng Fu; Dongyao Li; Qingqing Mu; Na Zhang; Yongsheng Sun; Miaoshu Wang; Hongtao Tian; Chen Li (Food Research International, 2026)

Comparative assessment of kinetic models for microbial inactivation in continuous-flow orange juice treated by induced electric field - Yaqian Fu; Zhang Huang; Na Yang; Yangchao Luo; Wenlong Liu; Baoqi Yin; Yamei Jin; Xueming Xu (Food Bioscience, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Metal coordination-hydrogen bonding synergistic cross-linked MXene for 3D-printed micro-supercapacitors in self-powered sensing systems - Haiyang Fu; Na Li; Yi Yuan; Zhaoyu Wang; Ling Wang; Simin Chai; Tengfei Duan; Jianxiong Xu (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Effects of flow-guiding block on water transport and performance in modified PEMFC gas flow channel - Lirong Fu; Baoshuo Yu; Shengwei Wu; Jinyi Liu; Huadong Lin; Na Qiu (Fuel, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Covalent organic framework nanospheres for solid-phase extraction of pyrethroids from vegetables - Weixin Duan; Na Liu; Xuechun Fu; Na Wang; Bo Cui (Food Chemistry, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Improving the flavor of protein hydrolysates from shrimp processing byproducts via maillard reaction: Towards structure-flavor relationship - Xiaoli Gong; Binbin Yu; Na Zhang; Soottawat Benjakul; Yuhao Zhang; Yu Fu (Food Chemistry, 2025)

Harpadon nehereus Peptide FF4 alleviates hyperuricemia by regulating uric acid synthetase and transporters, as well as modulating the ROS/NLRP3 signaling pathway - Yang-na Huang; Hui-wen Zheng; Sheng-xiang Zhao; Zhan-ying Zhu; Yong-jie Long; Yue-wen Chen; Jing-jing Fu (Food Bioscience, 2025)

Mechanisms for maintaining the stability of heterotrophic nitrification and aerobic denitrification in a synthetic microbial community under mixed nitrogen stress: Insights into community dynamics and metabolic features - Yuqi Qi; Minmin Chen; Chih-Huang Weng; Yanru Hao; Renchuan Fu; Xiao Liu; Chao Yan; Haolang Liu; Na Liu; Yaoming Su (Chemical Engineering Journal, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

Integrative multiomics elucidate crotonylation-associated GCDH in Parkinson’s disease pathogenesis via metabolome remodeling - Jia Fu; Jing Zhao; Na Mi; Chao Zhang; Yali Zhang; Lifen Yao (Mammalian Genome, 2025)

Ultrasonic high efficiency preparation of arctigenin from the fruits of Arctium lappa L using Aspergillus niger with deep eutectic solvent assisted - Yubin Ren; Shuang Jin; Weili Liu; Cailiang Peng; Hongyao Cai; Huayong Zhao; Yupeng Cheng; Yujie Fu; Na Zhang; Siyuan Wang; Chen Lv (Biotechnology Letters, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Investigating air-cushion effect in water-entry impact of notched-head blunt vehicles via the CFD-FEM coupling method - Zhe Zhang; Na-Na Yang; Wei Yang; Jin-Long Ju; Fu-Kui Gao; Wen-Hua Wu (Ocean Engineering, 2025)

Preparation high-efficiency NH2-MIL-125@g-C3N4 NADH photo-regeneration catalyst for enzymatic conversion of furfural to furfural alcohol - Shuaizhe Li; Xingyong Li; Senshen Yu; Qingtao Wang; Na Liu; Yichen Nie; Xuexiang Fu; Mengke Dong; Haolin Li; Yanliang Guo; Phidsavard Keomeesay; Shijie Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Facile design and construction for novel sequestrators via co–functionalization of Ti3AlC2 and biochar with nano-sized FeS in efficient selenite sequestration - Wei Wang; Hongxiang Wu; Xukun Ma; Mengqi Xu; Na Li; Jiajia Fu; Hongliang Dong (Journal of Environmental Chemical Engineering, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Titanium-based secondary nanotubes assembled from tiny nanocrystals for enhanced lithium and sodium storage - Huigui Wu; Yuju Zhu; Dongmei Liu; Kaihan Hu; Songyuan Sun; Na Fu; Jingbo Chen (Chemical Engineering Journal, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Pilot-scale evaluation of an efficient salt-free in-situ microemulsion for the remediation of multiple halogenated hydrocarbons-contaminated aquifers - Yu Yao; Yufeng Fu; Yongsheng Zhao; Na Liu; Huichao Xu; Dongyu Zhao; Wei Zhao; Hui Zhang; Chuanyu Qin (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Integrating microbial community dynamics and emerging contaminants (ECs) for precisely quantifying the sources in groundwater affected by livestock farming - Kai Liu; Jinrong Qiu; Chih-Huang Weng; Zhongen Tang; Renchuan Fu; Xiaojun Lin; Xiujuan Wang; Na Liu; Jingwen Zeng (Journal of Hazardous Materials, 2025)

Degradation of 2- (2-hydroxy-5-methylphenyl) benzotriazole (UV-P) by ferrate(VI): key factors, reaction pathway, and toxicity assessment - Xiaochen Qi; Fuli Li; Chih-Huang Weng; Kai Liu; Renchuan Fu; Na Liu; Longzhen Ding (Chemical Engineering Journal, 2025)

Duplication and Functional Diversification of ANP3-Like Genes (MAPKKKs) in Rosaceae - Yibo Sun; Fupeng Bian; Taishuai Cui; Tiansi Fu; Li Zhang; Na Gao; Qian Zhang; Muhammad Irfan; Xiaojia Zhang; Lijing Chen (Journal of Plant Growth Regulation, 2025)

Simultaneous detection of amino acids and short-chain fatty acids in tea using rapid pre-column derivatization coupled with GC–MS: Exploring their spatial distribution in tea trees and the impact of processing techniques on their content - Junren Xu; Jing Lu; Shanliang Fu; Na Li; Yiqiao Zhao; Kunbo Wang; Zhonghua Liu; Taolin Chen; Jianan Huang; Mingzhi Zhu (Food Chemistry, 2025)

The transcription factor CeWRI3 functions in TAG accumulation through activating CeOLE2 in Cyperus esculentus - Zhi Zou; Xiaowen Fu; Na Li; Panyan Zheng; Ruiling Wang; Hongyan Liu; Jiaquan Huang; Yongguo Zhao (Plant Cell Reports, 2025)

Composite geopolymer based on copper tailings: Mechanical properties, strength models and microstructure - Wei Wang; Pengfei Wei; Ping Jiang; Na Li; Fuyong Chu; Jiajia Fu; Xudong Wang (Journal of Environmental Chemical Engineering, 2025)

Rigid polyelectrolyte multilayer membrane with ultrahigh permeance and excellent dye/salt separation performance - Na Zhang; Fanglu Fu; Wen Bo; Hussein Baqiah; Li Zhao; Wenbo Lu; Yadi Cai; Jiahui Tian; Tingting Yan; Saisai Li; Shuyun Zheng; Qiang Li (Journal of Environmental Chemical Engineering, 2025)

The potential of food-derived peptides in alleviating depressed mood: Function, evaluation and mechanism - Yan Zhang; Yujia Lu; Yuchen Zhao; Wei Wu; Na Zhang; Yuhao Zhang; Yu Fu (Food Research International, 2025)

Improving the quality of frozen steamed stuffed buns after freeze-thaw cycles: Synergistic effects of cellulase, xylanase and sourdough - Zhao-Qiu Fu; Xiao-Hong Sun; Ke-Xue Zhu; Xiao-Na Guo (Food Bioscience, 2025)

Economic and environmental analysis: Straw biogas project operating at full load with dry yellow corn straw - Xiaotian Chen; Wei Fu; Kai Hu; Guofeng Yin; Song Liu; Na Zhu; Yehua Zhao; Zongjun Cui; Xufeng Yuan (Bioresource Technology, 2025)

Genetic Etiology Link to Brain Function Underlying ADHD Symptoms and its Interaction with Sleep Disturbance: An ABCD Study - Aichen Feng; Dongmei Zhi; Zening Fu; Shan Yu; Na Luo; Vince Calhoun; Jing Sui (Neuroscience Bulletin, 2025)

Sensor with Strong Solid Emission for Fluorescence Colormetric Detection of 1, 4-Dioxane in Water and Vapor Based on the Keto-Enol Isomerisation - Jing Wang; Zi-Ao Zong; Shi-Fu Huang; Mohd. Muddassir; Zhi-Yong Xing; Na-Na Li; Wen-Qiong Jiang (Journal of Fluorescence, 2025)

Insights into the mechanism of ameliorative antioxidant activity and hydration characteristics in cold plasma-induced glycosylated peanut protein products - Jiao-jiao Yu; Ran-ran Zhang; Da-Qiao Yang; Xiang-na Lin; Wen-jie Fu; Yi-qi Shao; Hui Ji; Zhan-yong Guo (Food Chemistry, 2025)

Associations of welding-related metals and hypertension in male welders: Roles of cytokinesis-block micronucleus cytome assay parameters - Xiayun Dai; Fan Wang; Yonggang Liao; Na Tu; Xiaolei Fu; Wenjuan Fu; Yizhe Sun; Junpin Liu; Siyu Wan; Wenjun Yin; Wei Pi; Jiaojun Liang; et al. (Environmental Pollution, 2025)

A dual-modification strategy for both the Quinone-based cathode and Zn anode electrodes of the aqueous zinc-ion battery - Mengyao Zhang; Jiahao Fu; Na Xu; Lei Meng (Chemical Engineering Journal, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Enrichment of a heterotrophic nitrifying and aerobic denitrifying bacterial consortium: Microbial community succession and nitrogen removal characteristics and mechanisms - Yuqi Qi; Renchuan Fu; Chao Yan; Xiao Liu; Na Liu (Bioresource Technology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Forest eco-function restoration and its positive effects on biodiversity improvement in China's ecological conservation programs - Jinyu Zhao; Xiao Fu; Na Sa; Xuyang Kou; Xiaojia He; Shuanning Zheng; Zhaohua Lu; Gang Wu; Weiguo Sang (Ecological Engineering, 2025)

Transcriptome-wide identification of MYB gene family and functional analysis of LcsMYB123 in Litsea coreana var. sinensis - Na Xie; Qiqiang Guo; Mengyun Liao; Yang Xiao; Chun Fu; Yunxin An (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Extracellular vesicles derived from “serum and glucose” deprived HUCMSCs promoted skin wound healing through enhanced angiogenesis - Xiaopeng Wu; Pingping Yuan; Na Wei; Chaoqun Ma; Mingdi Fu; Wei Wu (Molecular and Cellular Biochemistry, 2025)

The deformation characteristics of modified lightweight expanded polystyrene soils under cyclical loading - Ping Jiang; Yuming Fu; Wei Wang; Xuhui Zhou; Na Li; Huaqiang Tao (Soil Dynamics and Earthquake Engineering, 2025)

A boundary enforcement method for the truncated ship structure model during underwater contact explosion experiments - Liang Zhang; Xin Lin; Hong-Na Yang; Fu-Ren Ming (Ocean Engineering, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Induced electric field as alternative pasteurization to improve microbiological safety and quality of bayberry juice - Liping Xue; Zitao Zheng; Yuhang Wu; Lingtao Zhang; Huang Zhang; Na Yang; Xueming Xu; Yamei Jin; Man Meng; Fu Wang (Food Chemistry, 2025)

Breaking the vicious cycle of cellular senescence and ROS via a mitochondrial-targeted hydrogel for aged bone regeneration - Liangmin Fu; Shan Wang; Na Zhang; Yajing Lin; Shihui Zhang; Yingji Mao; Pinghui Zhou (Chemical Engineering Journal, 2025)

Study on the mechanism of SAR1B in sodium acetate promoting milk fat synthesis - Zhixia Wang; Haixin Fu; Na Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Effect of Germination on Mineral Content Changes in Brown Rice (Oryza sativa L.) - Xiang Li; Chunmin Ma; Xin Bian; Yu Fu; Guang Zhang; Xiaofei Liu; Na Zhang (Biological Trace Element Research, 2025)

An AIE-TICT fluorescence probe cascade responsive to H2S, polarity and viscosity to track microenvironment changes in cellular model of ischemia-reperfusion injury - Liguo Ji; Aoxiang Fu; Yuying Zhang; Ying Xu; Yanbei Xi; Shaoli Cui; Na Gao; Linlin Yang; Wanbing Shang; Zhijun Yang; Guangjie He (Analytica Chimica Acta, 2025)

Driving factor, source identification, and health risk of PFAS contamination in groundwater based on the self-organizing map - Jingwen Zeng; Kai Liu; Xiao Liu; Zhongen Tang; Xiujuan Wang; Renchuan Fu; Xiaojun Lin; Na Liu; Jinrong Qiu (Water Research, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

Construction of a BiOI/ZnO heterojunction on biomass Juncus effusus fiber for photodegradation of organic pollutants - Sijie Zhou; Na Zhu; Pei Lyu; Chunhua Zhang; Zhuan Fu; Junyao Gong; Zhaozixuan Zhou; Liangjun Xia (Journal of Environmental Sciences, 2024)

Transcriptomic reveals the effect of tannic acid stress on the cellular structure and growth of Saccharomyces cerevisiae - Yixin Huang; Mengfei Deng; Yanru Chen; Wenqin Cai; Na Liu; Yin Wan; Xiaodan Wu; Guiming Fu (Food Bioscience, 2024)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Fetal agenesis of corpus callosum: chromosomal copy number abnormalities and postnatal follow-up - Meiying Cai; Na Lin; Meimei Fu; Yanting Que; Hailong Huang; Liangpu Xu (Molecular Biology Reports, 2024)
Objective Agenesis of the corpus callosum (ACC) is an anomaly that can occur in fetuses during pregnancy. However, there is currently no treatment for fetal ACC. Therefore, we conducted a retrospective analysis of obstetric outcomes of fetal ACC to explore the relationship between fetal ACC phenotypes and chromosomal copy number abnormalities. Methods and results Amniotic fluid or umbilical cord blood were extracted from pregnant women with fetal ACC for karyotype analysis and chromosomal microarray analysis (CMA). Among the 48 fetuses with ACC, 22 (45.8%, 22/48) had isolated ACC, and 26 (54.2%, 26/48) had non-isolated ACC. Chromosomal abnormalities were detected via karyotype analysis in four cases. In addition to the four cases of pathogenic copy number variations (CNVs) detected using karyotype analysis, CMA revealed two cases of pathogenic CNVs with 17q12 microduplication and 16p12.2 microdeletion. The obstetric outcomes of 26 patients with non-isolated ACC were followed up, and 17 chose to terminate the pregnancy. In addition, seven of the nine cases with non-isolated ACC showed no obvious abnormality during postnatal follow-up, whereas only one case with normal CMA showed an abnormal phenotype at six months. Of the 22 patients with isolated ACC, six chose to terminate the pregnancy. Postnatal follow-up of 16 isolated ACC cases revealed only one with benign CNV, presenting with intellectual disability. Conclusion Pregnant women with fetal ACC should be offered prenatal CMA, particularly non-isolated ACC. Patients with ACC should undergo prolonged postnatal follow-up, and appropriate intervention should be provided if necessary.

Proteins from blue foods to meet the demand in the food sector: Editorial - Yu Fu; Na Zhang; Yuhao Zhang (Trends in Food Science & Technology, 2024)

Proteasome inhibition induces apoptosis through simultaneous inactivation of MCL-1/BCL-XL by NOXA independent of CHOP and JNK pathways - Wenjuan Chen; Mengning Sun; Yi Sun; Qinglan Yang; Hui Gao; Li Li; Rongrong Fu; Na Dong (Toxicology, 2024)

Degradation of thiosulfate ions in sodium aluminate solution photocatalyzed by Co-TiO2@ZIF-8 - Jingyi Hao; Binchuan Li; Jing Dai; Daxue Fu; Yongfeng Chang; Jianshe Chen; Na Xu; Kuiren Liu; Qing Han (Minerals Engineering, 2024)

Mechanisms of calcium-mediated As(V) immobilization by undissolved and dissolved biochar in saline-alkali environments - Na Liu; Ruili Gao; Jingjing Guo; Longwei Fu; Bin Xue; Kun Ma; Chen Lin (Journal of Environmental Management, 2024)

Towards food-derived self-assembling peptide-based hydrogels: Insights into preparation, characterization and mechanism - Chenxiao Zhu; Wei Wu; Olugbenga P. Soladoye; Na Zhang; Yuhao Zhang; Yu Fu (Food Chemistry, 2024)

Enhanced high-temperature energy storage performance in all-organic dielectric films through synergistic crosslinking of chemical and physical interaction - Xianhui Dong; Yan Wang; Yutong Cao; Na Li; Jiabin Fu; Yan Wang; Junrong Yu; Zuming Hu (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Long-term changes of surface ozone and ozone sensitivity over the North China Plain based on 2015–2021 satellite retrievals - Chuanyong Zhu; Yichao Gai; Zhenguo Liu; Lei Sun; Siyuan Fu; Kun Liu; Leifeng Yang; Guang Pan; Baolin Wang; Chen Wang; Na Yang; Zhisheng Li; et al. (Air Quality, Atmosphere & Health, 2024)

Toward the high-efficient utilization of poultry blood: Insights into functionality, bioactivity and functional components - Hanyuan Zheng; Shulei Zhao; Yujia Lu; Na Zhang; Olugbenga P. Soladoye; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2024)

Fourteen-year field experiment reveals neutral effects of N and P deposition on abundance and stoichiometric traits of the earthworm Pontoscolex corethrurus in tropical plantations - Zhifeng Shen; Xin Wang; Faming Wang; Jian Li; Jing Sun; Xiaoming Zou; Yiqing Li; Suli Li; Na Wang; Shenglei Fu; Weixin Zhang (Soil Biology and Biochemistry, 2024)

Preparation, pungency and bioactivity transduction of piperine from black pepper (Piper nigrum L.): A comprehensive review - Ruixuan Zou; Yuhao Zhou; Yujia Lu; Yuchen Zhao; Na Zhang; Jing Liu; Yuhao Zhang; Yu Fu (Food Chemistry, 2024)

Enhancing safe and effective treatment of carbapenem-resistant Klebsiella pneumoniae with polymyxin B-loaded dendritic nanoparticles - Wen Zhong; Yuyin Fu; Xukun Liao; Na Xu; Lingyi Shen; Jinglin Wu; Dan Zheng; Yadi Zhou; Lin Tan; Binyi Xia; Xinghua Fan; Meng Zhou; et al. (Chemical Engineering Journal, 2024)

Resveratrol suppresses liver cancer progression by downregulating AKR1C3: targeting HCC with HSA nanomaterial as a carrier to enhance therapeutic efficacy - Ying Wang; Longxiang Su; Zhansheng Hu; Shuang Peng; Na Li; Haiyan Fu; Baoquan Wang; Huiping Wu (Apoptosis, 2024)

Advances in the delivery and application of antimicrobial peptide-based nanomaterials - Haoran Deng; Shaohua Zhang; Yanxue Fu; Na Dong; Chongpeng Bi; Anshan Shan; Changxuan Shao (Chemical Engineering Journal, 2024)

Responses of the Arctic sea ice drift to general warming and intraseasonal oscillation in the local atmosphere - Ming Li; Xi Liang; Na Liu; Fu Zhao; Zhongxiang Tian (Climate Dynamics, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Two different types of hydrolases co-degrade ochratoxin A in a highly efficient degradation strain Lysobacter sp. CW239 - Xiaojie Fu; Qingru Fei; Xuanjun Zhang; Na Li; Liang Zhang; Yu Zhou (Journal of Hazardous Materials, 2024)

Functional properties and structure of soluble dietary fiber obtained from rice bran with steam explosion treatment - Xin-Yi Tian; Jian-Fu Liu; Cong-Cong Qiao; Zhuo Cheng; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2024)

Structure, thermal stability, physicochemical and functional characteristics of insoluble dietary fiber obtained from rice bran with steam explosion treatment: Effect of different steam pressure and particle size of rice bran - Xin-Yi Tian; Jian-Fu Liu; Zhuo Cheng; Na-Na Wu; Bin Tan (Food Research International, 2024)

Hydrochemical and microbial community characteristics and the sources of inorganic nitrogen in groundwater from different aquifers in Zhanjiang, Guangdong Province, China - Rentao Liu; Jinrong Qiu; Shuang Wang; Renchuan Fu; Xiaochen Qi; Chuanqi Jian; Qizhi Hu; Jingwen Zeng; Na Liu (Environmental Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Impact of greening trends on biogenic volatile organic compound emissions in China from 1985 to 2022: Contributions of afforestation projects - Yichao Gai; Lei Sun; Siyuan Fu; Chuanyong Zhu; Changtong Zhu; Renqiang Li; Zhenguo Liu; Baolin Wang; Chen Wang; Na Yang; Juan Li; Chongqing Xu; et al. (Science of The Total Environment, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

A preliminary understanding of the relationship between synthetic phenolic antioxidants and early pregnancy loss: Uncovering the potential molecular mechanisms - Yaqian Xu; Na Zhang; Yu Hu; Fu Chen; Ligang Hu; Chunyang Liao; Guibin Jiang (Science of The Total Environment, 2024)

The linkage between wintertime sea ice drift and atmospheric circulation in an Arctic ice-ocean coupled simulation - Xi Liang; Haibo Bi; Chengyan Liu; Xichen Li; Dakui Wang; Fu Zhao; Zhongxiang Tian; Ming Li; Na Liu (Ocean Modelling, 2024)

GC/MS-based untargeted metabolomics reveals the differential metabolites for discriminating vintage of Chenxiang-type baijiu - Na Wang; Lili Zhang; Li Fu; Mei Wang; Hui Zhang; Xiaoyu Jiang; Xiaohui Liu; Zhen Zhang; Xuejiao Ren (Food Research International, 2024)

Nutritional- and flavor-enhancing effects of biomass production by Rhodotorula spp. on cantaloupe juice - Ruitong Hou; Shuyu Liu; Na Lv; Baozhong Cui; Yongxue Wei; Feiyang Long; Hongfei Fu; Yunyang Wang (Food Bioscience, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Molecular Mechanism of Yangshen Maidong Decoction in the Treatment of Chronic Heart Failure based on Network Pharmacology, Molecular Docking, and Molecular Dynamics Simulations - Wei Cheng; Bo-Feng Zhang; Na Chen; Qun Liu; Xin Ma; Xiao Fu; Min Xu (Cell Biochemistry and Biophysics, 2024)

DPP8/9 inhibition attenuates the TGF-β1-induced excessive deposition of extracellular matrix (ECM) in human mesangial cells via Smad and Akt signaling pathways - Ke Li; Yuzhan Zhang; Weihao Zhao; Rongrong Wang; Yan Li; Linting Wei; Li Wang; Xianghui Chen; Zhao Chen; Pengfei Liu; Na Nie; Xuefei Tian; et al. (Toxicology Letters, 2024)

Confined fluid interfacial tension and minimum miscibility pressure prediction in shale nanopores - Qian Sun; Na Zhang; Peng Zhu; Wei Liu; Lingkong Guo; Shuoran Fu; Aabiskar Bhusal; Shuhua Wang (Fuel, 2024)

A near-infrared/tumor microenvironment dual-responsive cobalt-based material for photothermal/photodynamic/DNA-damaging chemotherapy synergistic therapy and anti-inflammation - Shuanglong Tang; Na An; Jing Luan; Xiaodan Wen; Yutuo Fu; Minghui Gao; Chongshen Guo (Chemical Engineering Journal, 2024)

Preparation, pungency and bioactivity of gingerols from ginger ( Zingiber officinale Roscoe): a review - Yuge Gao; Yujia Lu; Na Zhang; Chibuike C. Udenigwe; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2024)

Dynamic modeling of the occurrence, sources, and environmental behavior of polybrominated diphenyl ethers in Zhelin Bay, China - Jie Fu; Haibo Zhang; Ruijing Li; Hui Gao; Shuaichen Jin; Guangshui Na (Science of The Total Environment, 2024)

Structural characteristics and antioxidant activity of Chinese giant salamander enzymatic hydrolysate-glucose conjugates induced by ultrasound Maillard reaction - Jing-jing Fu; Fan-yu He; Xing-tong Zhu; Zhen Wang; Yang-na Huang; Jin-xiu Yu; Zhi-ping Wu; Yue-wen Chen (Food Bioscience, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Unraveling the mechanisms behind sodium persulphate-induced changes in petroleum-contaminated aquifers’ biogeochemical parameters and microbial communities - Yuqi Qi; Jun Zeng; Junshi Tao; Rentao Liu; Renchuan Fu; Chao Yan; Xiao Liu; Na Liu; Yanru Hao (Chemosphere, 2024)

Fate of organophosphate esters from the Northwestern Pacific to the Southern Ocean: Occurrence, distribution, and fugacity model simulation - Tengda Shi; Ruijing Li; Jie Fu; Chao Hou; Hui Gao; Guanjie Cheng; Haibo Zhang; Shuaichen Jin; Liang Kong; Guangshui Na (Journal of Environmental Sciences, 2024)

Enhanced strength, antioxidant and barrier properties of chitosan-based film by bentonite and lignosulfonate - Mengya Sun; Na Liu; Shuzhen Ni; Qinghua Xu; Hailong Gao; Hongqi Dai; Yingjuan Fu; Menghua Qin (Food Packaging and Shelf Life, 2024)

Evaluating the potential of different bioaugmented strains to enhance methane production during thermophilic anaerobic digestion of food waste - Na Wang; Mengyao Xiao; Siying Zhang; Xiaomiao Chen; Jingjing Shi; Shanfei Fu; Jiping Shi; Li Liu (Environmental Research, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

ACT001 alleviates inflammation and pyroptosis through the PPAR-γ/NF-κB signaling pathway in LPS-induced alveolar macrophages - Qiang Fu; Na Shen; Tao Fang; Hewei Zhang; Yanbo Di; Xuan Liu; Chao Du; Jianshuang Guo (Genes & Genomics, 2024)

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

Accident case data-accident causation model driven safety training method: Targeted safety training empowered by historical accident data in coal industry - Xie Xuecai; Fu Gui; Shen Shifei; Shu Xueming; Li Jing; Huang Lida; Wei Na (Process Safety and Environmental Protection, 2024)

Combining microbiome and pseudotargeted metabolomics revealed the alleviative mechanism of Cupriavidus sp. WS2 on the cadmium toxicity in Vicia unijuga A.Br. - Xuefeng Yuan; Dandan Wu; Dingguo Zhang; Chunyu He; Zilong Wang; Wenqian Xu; Na Shou; Keyi Fu; Mingyuan Yue; Xin Zhang; Zunji Shi (Environmental Pollution, 2024)

Efficient data-driven prediction of household carbon footprint in China with limited features - Na An; Chenyu Huang; Yanting Shen; Jinyu Wang; Zhongqi Yu; Jiayan Fu; Xiao Liu; Jiawei Yao (Energy Policy, 2024)

Effect of long-term straw return on organic matter transformation by hydroxyl radical during paddy soil oxygenation - Yanqi Xiao; Wei Peng; Junhong Fu; Yaqi Ning; Hao-jie Cui; Dong Cheng; Na Zhang; Weijun Zhou; Wenjuan Liao (Chemical Engineering Journal, 2024)

Traditional Chinese medicine residue enzymatic hydrolysates for production of polyhydroxyalkanoate by newly isolated Bacillus altitudinis - Xinyue Li; Jing Chen; Yahui Liu; Shuangqing Fu; Peixun Zhang; Na Zhang; Wei Li; Honglei Zhang (Bioresource Technology, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Hydroxy fatty acids in the surface Earth system - Wenxin Zhang; Wei Hu; Quanfei Zhu; Mutong Niu; Na An; Yuqi Feng; Kimitaka Kawamura; Pingqing Fu (Science of The Total Environment, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Research progress of anti-environmental factor stress mechanism and anti-stress tolerance way of Saccharomyces cerevisiae during the brewing process - Yanru Chen; Yili Yang; Wenqin Cai; Jiali Zeng; Na Liu; Yin Wan; Guiming Fu (Critical Reviews in Food Science and Nutrition, 2023)

Comparison of the environmental impact of typical packaging systems for food cold chain express based on life cycle assessment - Teng Meng; Yinpu Wang; Lin Fu; Yuelin Wang; Na Zhang; Zhao Wang; Qi Yang (Journal of Cleaner Production, 2023)

Construction of multiple channels for electron transport in In2S3/In2O3/rGO heterojunctions to boost photocatalytic CO2 conversion to C2+ hydrocarbons - Yipin Zhang; Wenjuan Li; Fu Tian; Na Cai; Qinhui Guan; Dapeng Zhang; Weiguang Ran; Na Li; Tingjiang Yan (Chemical Engineering Journal, 2023)

Long period changes of hippocampal diffusion kurtosis imaging and its correlation with cognitive dysfunction after incomplete cerebral ischemia–reperfusion in rats - Lan Fu; Lin-Na Guan; Hongye Zuo (Experimental Brain Research, 2023)

How does a celiac iceberg really float? The relationship between celiac disease and gluten - Xiaoxue Zhu; Xin-Huai Zhao; Qiang Zhang; Na Zhang; Olugbenga P. Soladoye; Rotimi E. Aluko; Yuhao Zhang; Yu Fu (Critical Reviews in Food Science and Nutrition, 2023)

Discovery and identification of a novel canine coronavirus causing a diarrhea outbreak in Vulpes - Yuting Liu; Yao Deng; Sheng Niu; Na Zhu; Jingdong Song; Xiaoshuang Zhang; Weiting Su; Wenhui Nie; Roujian Lu; David M. Irwin; George Fu Gao; Wenling Wang; et al. (Science Bulletin, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Corrigendum to “In-situ self-assembled vaccine constructed with dual switchable nanotransformer for tumor immunotherapy” [Chem. Eng. J. 454 (2023) 140190] - Zipeng Zhang; Shuang Liang; Shunli Fu; Tong Gao; Weiwei Mu; Lili Chang; Shujun Liu; Yongjun Liu; Na Zhang (Chemical Engineering Journal, 2023)

Codonopsis pilosula polysaccharides promote osteogenic differentiation and inhibit lipogenic differentiation of rat bone marrow stem cells by activating β-catenin - Jinjin Liu; Jinyang An; Na Jiang; Kuan Yang; Conghui Guan; Nan Zhao; Jianguo Cheng; Songbo Fu; Chengxu Ma; Xiaoni Ma; Xulei Tang (Chemico-Biological Interactions, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

Occurrence, source, and transfer fluxes of organophosphate esters in the South Pacific and Fildes Peninsula, Antarctic - Ruijing Li; Hui Gao; Chao Hou; Jie Fu; Tengda Shi; Zilan Wu; Shuaichen Jin; Ziwei Yao; Guangshui Na; Xindong Ma (Science of The Total Environment, 2023)

Ultralow-background SERS substrates for reliable identification of organic pollutants and degradation intermediates - Longfei Zhang; Rongfang Zhao; Yanzhou Wu; Zhiyang Zhang; Yan Chen; Meichun Liu; Na Zhou; Yunqing Wang; Xiuli Fu; Xuming Zhuang; Jianping Wang; Lingxin Chen (Journal of Hazardous Materials, 2023)

Carboxyl-containing components delineation via feature-based molecular networking: A key to processing conditions of fermented soybean - Yuye Gao; Yu Fu; Na Li; Yuetong Jiang; Xiaojing Liu; Congcong Gao; Lishuang Wang; Jian-Lin Wu; Tingting Zhou (Food Chemistry, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Spatial distribution, source, and ecological risk of polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecanes (HBCDs) in Jiaozhou Bay, China - Jie Fu; Haibo Zhang; Ruijing Li; Tengda Shi; Lisha Wang; Guanjie Cheng; Jiajin Huang; Shisheng Li; Hui Gao; Shuaichen Jin; Guangshui Na (Marine Pollution Bulletin, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Antibiotic residues of drinking-water and its human exposure risk assessment in rural Eastern China - Yingying Wang; Xiaolian Dong; Jinxin Zang; Xinping Zhao; Feng Jiang; Lufang Jiang; Chenglong Xiong; Na Wang; Chaowei Fu (Water Research, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Upgrading the accumulation of ginsenoside Rd in Panax notoginseng by a novel glycosidase-producing endophytic fungus G11-7 - Lili Niu; Xiangyu Qin; Litao Wang; Na Guo; Hongyan Cao; Hanghang Li; Chunjian Zhao; Huimei Wang; Yujie Fu (Folia Microbiologica, 2023)

Aspergillus sp. R3, a new producer for cyclopyazonic acid, inhibits rice sheath blight fungus Rhizoctonia solani Kühn - Xiangyu Qin; Yuanhang Chang; Yao Wang; Jie Yang; Siming Nie; Na Guo; Jian Xu; Fengkun Cai; Chunjian Zhao; Yujie Fu (Physiological and Molecular Plant Pathology, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Geochemical characteristics of shales from Upper Carboniferous Yanghugou formation in Weiningbeishan area, China: Implication for provenance, source weathering and tectonic setting - Yu Ma; Hongze Yang; Yanyun Ma; Yongping Wang; Wenzhong Wu; Na An; Shuofeng Tian; Ling Ma; Deliang Fu (Marine and Petroleum Geology, 2023)

Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill - Xin-Yu Yan; Zi-Hui Cai; Peng-Quan Zhao; Jian-Dong Wang; Li-Na Fu; Qi Gu; Yu-Jie Fu (Food Research International, 2023)

A universal strategy for large-scale and controlled fabrication of conductive mesoporous polymer monolayers - Facai Wei; Bowen Chen; Jianwei Fu; Qingguo He; Chengbin Jing; Jiangong Cheng; Miharu Eguchi; Jongbeom Na; Yusuke Yamauchi; Shaohua Liu (Chemical Engineering Journal, 2023)

A statistical analysis of conjugate equatorial plasma bubbles based on 630 nm airglow observations - Zukang Dai; Tao Yu; Na Yang; Jin Wang; Di Fu; Xiangpeng Feng; Yutao Feng (Science China Earth Sciences, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Kynurenic acid mediates bacteria-algae consortium in resisting environmental cadmium toxicity - Xiaoli Qi; Keyi Fu; Mingyuan Yue; Na Shou; Xuefeng Yuan; Xi Chen; Chunyu He; Yunfeng Yang; Zunji Shi (Journal of Hazardous Materials, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

In-situ self-assembled vaccine constructed with dual switchable nanotransformer for tumor immunotherapy - Zipeng Zhang; Shuang Liang; Shunli Fu; Tong Gao; Weiwei Mu; Lili Chang; Shujun Liu; Yongjun Liu; Na Zhang (Chemical Engineering Journal, 2023)

Occurrence, spatial patterns, air-seawater exchange, and atmospheric deposition of polycyclic aromatic hydrocarbons (PAHs) from the Northwest Pacific to Arctic Ocean - Jie Fu; Haibo Zhang; Ruijing Li; Tengda Shi; Hui Gao; Shuaichen Jin; Qian Wang; Humin Zong; Guangshui Na (Marine Environmental Research, 2023)

Correction to: Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2023)

Establishment and Optimization of Soil Cd Risk Threshold in Typical Karst Area with Potato Production, China - Hu Wang; Na Cai; Sitong Gong; Jiajia Zhou; Tengbing He; Bing Wang; Tianling Fu (Bulletin of Environmental Contamination and Toxicology, 2023)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

The Role of PTEN/PI3K/AKT Signaling Pathway in Apoptosis of Liver Cells in Cocks with Manganese Toxicity - Liu Xiaofei; Hou Yan; Fu Yu; Fan Jing; Yangyang; Zhang Na (Biological Trace Element Research, 2022)

Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Dongxue Li; Yi’na Li; Yiliang Xie; Baoshan Cui; Zhonghua Ning; Shuyan Zhang; Zhenggang Bi; Shouqiang Fu; Chunguang Che (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the contents of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest content in the North Unrestoration, while the TS content appeared highest in the North Restoration. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, the changing trend of soil C/S in the North Unrestoration exhibited a considerably different profile similarity from the North Restoration, which indicates that the ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the high content of soil biogenic elements SOC and high ratio of soil ecological stoichiometry C/N and C/S in the Yellow River Delta induce that they are more sensitive to environmental change. Over the three years, the contributions of soil moisture content, soil salinity, and pH to soil biogenic element contents and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally has a positive effect on the soil biogenic element contents and their ecological stoichiometry in the Yellow River Delta and provides a reference for delta restoration.

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Non-peer-reviewed data, effect measures, and meta-regression analysis on proton pump inhibitor use and COVID-19 - Dan-Na Wu; Li-Rong Jiao; Guo-Fu Li; Guo Yu (European Journal of Clinical Pharmacology, 2022)

14-3-3β is essential for milk composition stimulated by Leu/IGF-1 via IGF1R signaling pathway in BMECs - Hui Cao; Guan Huang; Haixin Fu; Na Zhang (In Vitro Cellular & Developmental Biology - Animal, 2022)

The altered functional modular organization in systemic lupus erythematosus: an independent component analysis study - Zheng-Ye Cao; Na Wang; Hua Wei; Jie-Ting Jia; Hong-Ying Zhang; Song-An Shang; Qing-Qiang Zhu; Xian-Fu Luo; Jing-Tao Wu (Brain Imaging and Behavior, 2022)

Qingbo, a common cyprinid fish, responds diversely in behavior and locomotion to predators with different hunting modes - Cheng Fu; Lian-Chun Yi; Wen-Pei Wu; Chun-Xiao Sun; Rui-Na Liu; Shi-Jian Fu (Fish Physiology and Biochemistry, 2021)

Evaluating changes in ecological land and effect of protecting important ecological spaces in China - Jixi Gao; Xiaoman Liu; Chao Wang; Yong Wang; Zhuo Fu; Peng Hou; Na Lyu (Journal of Geographical Sciences, 2021)

Incidence and Mortality of Acute Disseminated Encephalomyelitis in China: A Nationwide Population-Based Study - Yuwen Xiu; Hongqiu Gu; Xindi Li; Zixiao Li; Wei-Na Jin; Qiang Liu; Fu-Dong Shi (Neuroscience Bulletin, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Pollution characteristics and risk assessment of surface sediments in the urban lakes - Na Cheng; Laisheng Liu; Zelin Hou; Jiapeng Wu; Qiwen Wang; Yicheng Fu (Environmental Science and Pollution Research, 2021)

microRNA-184 enhances the sensitivity of pheochromocytoma-12 cells to doxorubicin by targeting ADAM22 - Nairui Zhao; Na Su; Guangya Wang; Dongxia Fu; Fang Gao; Yunna Zhang (Molecular & Cellular Toxicology, 2021)

Respiratory Control by Phox2b-expressing Neurons in a Locus Coeruleus–preBötzinger Complex Circuit - Na Liu; Congrui Fu; Hongxiao Yu; Yakun Wang; Luo Shi; Yinchao Hao; Fang Yuan; Xiangjian Zhang; Sheng Wang (Neuroscience Bulletin, 2021)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Transcriptional profiling of underground interaction of two contrasting sunflower cultivars with the root parasitic weed Orobanche cumana - Chong Yang; Fei Fu; Na Zhang; Jiansu Wang; Luyang Hu; Faisal Islam; Quanjiang Bai; Xiaopeng Yun; Weijun Zhou (Plant and Soil, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Effects of total dissolved gas supersaturated water at varying suspended sediment concentrations on the survival of rock carp Procypris rabaudi - Cuixia Feng; Na Li; Yuanming Wang; Xiaoqing Liu; Xiaotao Shi; Chenghua Fu; Zhu Jiang; Yao Yang; Haoran Shi (Fisheries Science, 2019)

Removal of chromium(VI) by MnFe2O4 and ferrous ion: synergetic effects and reaction mechanism - Na Li; Weibin Li; Fenglian Fu (Environmental Science and Pollution Research, 2019)

Water entry in jujube fruit and its relationship with cracking - Na Li; Lijiao Fu; Yuqin Song; Jie Li; Xiaofang Xue; Shuran Li; Liulin Li (Acta Physiologiae Plantarum, 2019)

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

Dynamic Response of Offshore Open-Ended Pile under Lateral Cyclic Loadings - Junwei Liu; Zhen Guo; Na Zhu; Hui Zhao; Ankit Garg; Longfei Xu; Tao Liu; Changchun Fu (Journal of Marine Science and Engineering, 2019)
Foundations for offshore wind turbines (OWTs) are mainly open-ended piles that are subjected to cyclic loadings caused by winds, waves and currents. This study aims to investigate the dynamic responses of open-ended pipe pile under lateral cyclic loadings, as well as the characteristics of the soil plug and surrounding soil. Both large-scale indoor model test and discrete element simulation were adopted in this study. The test results show that the resistance of each part of the pipe pile increases linearly with depth during the process of pile driving. The pile side resistance degradation effect was also observed along with the friction fatigue. The soil plug formation rate decreases gradually with an increase in the pile depth. The influence range in the surrounding soil is about 5~6 times of the pile diameter. The cumulative displacement of the pile head increases with the number of cycles. Lateral tangential stiffness and lateral ultimate bearing capacity decreases with an increase in number of cycles. The severe disturbance range of soil around the pile is 2~3 times of the pile diameter. The center of rotation of the pile body is about 0.8 times of the pile body depth. The side frictional resistance and lateral pressure of the pile body is found to fluctuate along the pile body. Additionally, the lateral pressure and side friction resistance decreases gradually with decreasing tendency of the former more than the latter.

Vascularized composite allograft rejection is delayed by infusion of IFN-γ-conditioned BMSCs through upregulating PD-L1 - Yaojun Wang; Yunfeng Xi; Fu Han; Yang Liu; Na Li; Zhongliang Ren; Jiajie Xue; Lei Guo; Dahai Hu (Cell and Tissue Research, 2019)

Dexamethasone protects the glycocalyx on the kidney microvascular endothelium during severe acute pancreatitis - Wen-qiao Yu; Shao-yang Zhang; Shui-qiao Fu; Qing-hui Fu; Wei-na Lu; Jian Zhang; Zhong-yan Liang; Yun Zhang; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2019)

Evoked potential study of the inferior collicular response to constant frequency-frequency modulation (CF-FM) sounds in FM and CF-FM bats - Ziying Fu; Na Xu; Guimin Zhang; Dandan Zhou; Long Liu; Jia Tang; Philip Hung-Sun Jen; Qicai Chen (Journal of Comparative Physiology A, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

Transcriptomics and metabonomics analyses of maternal DEHP exposure on male offspring - Yunbo Zhang; Wanying Zhang; Xihang Fu; Fenfen Zhou; Haiyang Yu; Xiaolin Na (Environmental Science and Pollution Research, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Spatiotemporal variability of precipitation during 1961–2014 across the Mongolian Plateau - Fu-ying Qin; Gen-suo Jia; Jie Yang; Yin-tai Na; Mei-ting Hou; Narenmandula (Journal of Mountain Science, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Geochemistry and petrogenesis of Triassic mineralized porphyries in the Geza of the Sanjiang orogenic belt, southwestern China - Xue-long Liu; Wen-chang Li; Na Zhang; Fu-cheng Yang (International Geology Review, 2017)

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Effects of optimized root water uptake parameterization schemes on water and heat flux simulation in a maize agroecosystem - Fu Cai; Huiqing Ming; Na Mi; Yanbing Xie; Yushu Zhang; Rongping Li (Journal of Meteorological Research, 2017)

Identification and functional analysis of the GTPV bidirectional promoter region - Hui Zhang; Zhihua Sun; Na Zhang; Zhiqiang Li; Pengyan Wang; Qiang Fu; Yan Ren; Xuehua Shao; Yu Zhang; Zhiru Guo; Chuangfu Chen (Archives of Microbiology, 2017)

RNA-Seq Analysis of the Antioxidant Status and Immune Response of Portunus trituberculatus Following Aerial Exposure - Yuquan Li; Shoumin Lai; Renjie Wang; Yuchao Zhao; Hao Qin; Lingxu Jiang; Na Li; Qiang Fu; Chao Li (Marine Biotechnology, 2017)

Characterization of Batai virus isolated from a domestic Muscovy duck (Cairina moschate) - Lijiao Zhang; Qingshui Zhang; Jun Wang; Na An; Yanxin Cao; Guanghua Fu; Xueying Hu; Yu Huang; Jingliang Su (Virus Genes, 2017)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Double-stranded-RNA-specific adenosine deaminase 1 (ADAR1) is proposed to contribute to the adaptation of equine infectious anemia virus from horses to donkeys - Yan-Dong Tang; Xiang Zhang; Lei Na; Xue-feng Wang; Li-Hua Fu; Chun-Hui Zhu; Xiaojun Wang; Jian-Hua Zhou (Archives of Virology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Genome-wide identification and comparative analysis of grafting-responsive mRNA in watermelon grafted onto bottle gourd and squash rootstocks by high-throughput sequencing - Na Liu; Jinghua Yang; Xinxing Fu; Li Zhang; Kai Tang; Kateta Malangisha Guy; Zhongyuan Hu; Shaogui Guo; Yong Xu; Mingfang Zhang (Molecular Genetics and Genomics, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Smad signal pathway regulates angiogenesis via endothelial cell in an adipose-derived stromal cell/endothelial cell co-culture, 3D gel model - Shiyu Lin; Jing Xie; Tao Gong; Sirong Shi; Tao Zhang; Na Fu; Yunfeng Lin (Molecular and Cellular Biochemistry, 2016)

Effects of heat stress on serum Cortisol, alkaline phosphatase activity and heat shock protein 40 and 90β mRNA expression in rainbow trout Oncorhynchus mykiss - Zhen Li; Zhe Liu; Yan Ni Wang; Yu Jun Kang; Jian Fu Wang; Hai Na Shi; Jin Qiang Huang; Li Jiang (Biologia, 2016)

Retraction Note to: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2015)

Characterization and expression analysis of Calmodulin (CaM) in orange-spotted grouper (Epinephelus coioides) in response to Vibrio alginolyticus challenge - Sheng-Wei Luo; Fu-Xing Xie; Yuan Liu; Wei-Na Wang (Ecotoxicology, 2015)

iTRAQ-based quantitative proteomic analysis of longissimus muscle from growing pigs with dietary supplementation of non-starch polysaccharide enzymes - Ji-ze Zhang; Yang Gao; Qing-ping Lu; Ren-na Sa; Hong-fu Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Isolation and characterization of fourteen microsatellite loci for Asiatic toad (Bufo gargarizans) at high altitude through transcriptome sequencing - Na Li; Guannan Wen; Weizhao Yang; Jinzhong Fu (Conservation Genetics Resources, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

An anther development F-box (ADF) protein regulated by tapetum degeneration retardation (TDR) controls rice anther development - Li Li; Yixing Li; Shufeng Song; Huafeng Deng; Na Li; Xiqin Fu; Guanghui Chen; Longping Yuan (Planta, 2015)

The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control - Jing-Yu He; Na Ma; Shu Zhu; Katsuko Komatsu; Zhi-Yuan Li; Wei-Ming Fu (Journal of Natural Medicines, 2015)
Codonopsis , in the family Campanulaceae, is a genus containing 42 species of dicotyledonous herbaceous perennial plants, predominantly found in Central, East and South Asia. Several Codonopsis species are widely used in traditional medicine and are considered to have multiple medicinal properties. Among the Codonopsis species, Codonopsis pilosula (Franch.) Nannf. and C. lanceolata (Sieb. et Zucc.) Benth. & Hook. f. ex Trautv. are more popular than others according to the findings, especially phytochemical and bioactive studies. Phytochemical research shows that Codonopsis species contain mainly polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities. However, the mechanisms of their bioactivities need to be further elucidated. The less popular Codonopsis species remain to be studied and exploited. In addition, although a series of methods for the quality evaluation of Codonopsis species have been developed, a feasible and reliable approach to the efficacious and safe use of various Codonopsis species is still needed, with considering botanical origin, chemical constituents and bioactive effects. This review aims to provide up-to-date and comprehensive information on the phytochemistry, bioactivity and quality control of medicinal plants in the genus Codonopsis and to highlight current gaps in knowledge, which is useful for the wider development of the Codonopsis genus.

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Synthesis and cytotoxic activities of novel bergenin derivatives - Na-Na Liu; Fu-Kai Bao; Jing-Bo Chen; Xiang-Hui Zeng; Shui-Jing Chi; Jian-Ping Liu (Medicinal Chemistry Research, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

Copper toxicity to Phaeodactylum tricornutum: a survey of the sensitivity of various toxicity endpoints at the physiological, biochemical, molecular and structural levels - Yong Wei; Na Zhu; Michel Lavoie; Jiaying Wang; Haifeng Qian; Zhengwei Fu (BioMetals, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

RETRACTED ARTICLE: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Black band disease as a possible factor of the coral decline at the northern reef-flat of Yongxing Island, South China Sea - HongQiang Yang; JianWei Shen; FeiXue Fu; Yue Wang; Na Zhao (Science China Earth Sciences, 2014)

Identifying novel salt-tolerant genes from Dunaliella salina using a Haematococcus pluvialis expression system - Wen-fang Gong; Li-na Zhao; Bin Hu; Xi-wen Chen; Feng Zhang; Zheng-mao Zhu; De-fu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Is there a role of TNFR1 in acute lung injury cases associated with extracorporeal circulation? - Yu Zhao; Chong-wei Zhang; Wen-jing Zhou; Jiao Chen; Nan-fu Luo; Li-na Gong; Lei Du; Jing Zhou (Journal of Zhejiang University-SCIENCE B, 2014)

Contribution of arbuscular mycorrhizal fungi to the development of maize (Zea mays L.) grown in three types of coal mine spoils - Wei Guo; Renxin Zhao; Ruiying Fu; Na Bi; Lixin Wang; Wenjing Zhao; Jiangyuan Guo; Jun Zhang (Environmental Science and Pollution Research, 2014)

High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Coral community dynamics and shallow-water carbonate deposition of the reef-flat around Yongxing Island, the Xisha Islands - JianWei Shen; HongQiang Yang; Yue Wang; FeiXue Fu; Na Zhao (Science China Earth Sciences, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

pmX: a recessive powdery mildew resistance gene at the Pm4 locus identified in wheat landrace Xiaohongpi - Bisheng Fu; Yang Chen; Na Li; Hongqi Ma; Zhongxin Kong; Lixia Zhang; Haiyan Jia; Zhengqiang Ma (Theoretical and Applied Genetics, 2013)

The flavonoid content in leaves and inflorescences of the wild perennial Fagopyrum cymosum complex - Na Liu; Friedrich Josef Zeller; Qing-Fu Chen (Genetic Resources and Crop Evolution, 2013)

Molecular Cloning and Polymorphism of the Major Histocompatibility Complex (MHC) Class IIB Gene of Grass Carp (Ctenopharyngodon idella) - Zhong-Dian Dong; Yan Zhao; Qi Fan Zeng; Yong Fu; Fen Na Zhou; Xiang Shan Ji; Hui Wang (Biochemical Genetics, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Roseibacterium beibuensis sp. nov., a Novel Member of Roseobacter Clade Isolated from Beibu Gulf in the South China Sea - Yujiao Mao; Jingjing Wei; Qiang Zheng; Na Xiao; Qipei Li; Yingnan Fu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

ACE2 gene polymorphism and essential hypertension: an updated meta-analysis involving 11,051 subjects - Na Lu; Yang Yang; Yibo Wang; Yan Liu; Gang Fu; Dongmei Chen; Hui Dai; Xiaohan Fan; Rutai Hui; Yang Zheng (Molecular Biology Reports, 2012)

Statistical characteristics of austral summer cyclones in Southern Ocean - Na Liu; Gang Fu; Ying-Hwa Kuo (Journal of Ocean University of China, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

Mutations in isocitrate dehydrogenase 2 accelerate glioma cell migration via matrix metalloproteinase-2 and 9 - Yuejun Fu; Yali Zheng; Ke Li; Rui Huang; Shuhua Zheng; Na An; Aihua Liang (Biotechnology Letters, 2012)

A potential strategy for high-grade gliomas: combination treatment with lithium chloride and BmK CT - Yuejun Fu; Shuhua Zheng; Rui Huang; Na An; Yali Zheng; Zhiyun Zhang; Aihua Liang (Biotechnology Letters, 2012)

Origin of hydrogen peroxide during the cowpea- Xanthomonas interaction - Yan Zhu; Yanhong Li; Ronghui Hu; Yani Zheng; Na Feng; Fu Chen; Jing Wang; Hongyu Li (Australasian Plant Pathology, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

Identification and mapping of a new powdery mildew resistance gene on chromosome 6D of common wheat - Hongqi Ma; Zhongxin Kong; Bisheng Fu; Na Li; Lixia Zhang; Haiyan Jia; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

A model of BmK CT in inhibiting glioma cell migration via matrix metalloproteinase-2 from experimental and molecular dynamics simulation study - Yue-Jun Fu; Na An; Kok-Gan Chan; Yan-Bo Wu; Shu-Hua Zheng; Ai-Hua Liang (Biotechnology Letters, 2011)

Reagentless biosensor based on layer-by-layer assembly of functional multiwall carbon nanotubes and enzyme-mediator biocomposite - Xing-hua Zhou; Feng-na Xi; Yi-ming Zhang; Xian-fu Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular authentication of geo-authentic Scrophularia ningpoensis - Chuan Chen; Li-na Duan; Xiao-long Zhou; Bing-long Chen; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2011)

Optimized procedure for expression and renaturation of recombinant human bone morphogenetic protein-2 at high protein concentrations - Hongbin Zhang; Jie Wu; Yu Zhang; Na Fu; Jie Wang; Shujin Zhao (Molecular Biology Reports, 2010)

Osteogenic role of endosomal chloride channels in MC3T3-E1 cells - Huan Wang; Na Huo; Feifei Li; Shanmin Fu; Yang Xue; Ting Yang; Xuan Wen; Yin Ding; Xiaohong Duan (Molecular and Cellular Biochemistry, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Molecular cloning and characterization of hatching enzyme-like gene in the silkworm, Bombyx mori - Fu-hao Lu; Shun-ming Tang; Xing-jia Shen; Na Wang; Qiao-ling Zhao; Guo-zheng Zhang; Xi-jie Guo (Molecular Biology Reports, 2010)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A Facile Method for Preparation of Polymerizable, Optically Active Ketoprofen Prodrug by Irreversible Lipase-catalysed Resolution - Xiao-Qing Cai; Zhi-Chun Chen; Na Wang; Xian-Fu Lin (World Journal of Microbiology and Biotechnology, 2006)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

Regioselective Enzymatic Synthesis of Non-Steroidal Anti-Inflammatory Drugs Containing Glucose in Organic Media - Na Wang; Bo Kai Liu; Qi Wu; Jun Liang Wang; Xian Fu Lin (Biotechnology Letters, 2005)

Regioselective enzymatic acylation of ribavirin to give potential multifunctional derivatives - Bo-Kai Liu; Na Wang; Qi Wu; Chuan-Ying Xie; Xian-Fu Lin (Biotechnology Letters, 2005)

Novel mutual pro-drugs of 2?,3?-dideoxyinosine with 3-octadecyloxy-propane-1,2-diol by straightforward enzymatic regioselective synthesis in acetone - Xiao-Feng Sun; Qi Wu; Na Wang; Ying Cai; Xian-Fu Lin (Biotechnology Letters, 2005)

Controllable regioselective enzymatic synthesis of polymerizable 5′-O-vinyl- and 3′-O-vinyl-nucleoside analogues in acetone - Xiao-Feng Sun; Na Wang; Qi Wu; Xian-Fu Lin (Biotechnology Letters, 2004)